Multiethnic Genome-Wide Association Study of Cerebral White Matter Hyperintensities on MRI. (April 2015) - Verhaaren, Benjamin F.J.; Debette, Stéphanie; Bis, Joshua C.; Smith, Jennifer A.; Ikram, M. Kamran; Adams, Hieab H.; Beecham, Ashley H.; Rajan, Kumar B.; Lopez, Lorna M.; Barral, Sandra; van Buchem, Mark A.; van der Grond, Jeroen; et al.
<x xml:space="preserve">Abstract</x> Background— The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. Methods and Results— We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10−19) and identified novel loci on chr10q24 (P=1.6×10−9) and chr2p21 (P=4.4×10−8). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10−8) and chr2p16 (P=1.5×10−8). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). Conclusions— We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.